Developing creative and dynamic reading activities to increase students´ attention span-a case study in 8-9 year old children at ABC English Institute - Jarrín Escobar, Verónica Gissela (2008)
1. Theoretical framework. 2.Methodology. 3.Analysis and interpretation of results. 4.Creative and dynamic reading activities to increase students´ attention span in 8-9 year old children at ABC English Institute 5.Conclusions and recommendations